Correlations Between Tumor Mutation Burden and Immunocyte Infiltration and Their Prognostic Value in Colon Cancer - Zhou, Zhangjian; Xie, Xin; Wang, Xuan; Zhang, Xin; Li, Wenxin; Sun, Tuanhe; Cai, Yifan; Wu, Jianhua; Dang, Chengxue; Zhang, Hao (Frontiers in Genetics, 2021)
Background: Colon cancer causes huge incidence and mortality worldwide every year. Immunotherapy could be a new therapeutic opinion for advanced colon cancer patients. Tumor mutation burden (TMB) and immune infiltration are considered critical in immunotherapy but their characteristics among colon cancer are still controversial. Methods: The somatic mutation, transcriptome and clinical data of colon cancer patients were obtained from TCGA database. Patients were divided into low or high TMB groups by the median TMB value. Somatic mutation landscape, differential expressed genes and immune-related hub genes, Gene Ontology and KEGG, gene set enrichment and immune infiltration analyses were investigated between two TMB groups. Univariate and multivariate Cox analysis were utilized to construct a prognostic gene signature. The differences in immune infiltration, expression of HLA related genes and checkpoint genes were investigated between two immunity groups based on single sample gene set enrichment analysis. Finally, a nomogram prognostic predicting model integrating TMB, immune infiltration and clinical parameters was established. Calibration plots and receiver operating characteristic curve were drawn and C-index was calculated to assess the predictive ability. Results: Missense mutation and single nucleotide polymorphism were the major variant characteristics in colon cancer. The TMB level showed significant differences in N stage, M stage, pathological stage and immune infiltration. CD8+ T cells, activated memory CD4+ T cells, activated NK cells and M1 macrophages infiltrated more in high-TMB group. Antigen processing and presentation signaling pathway was enriched in high-TMB group. Two immune related genes (CHGB and SCT) were identified to be correlated with colon cancer’s survival (HR=1.39, P=0.01; HR=1.26, P=0.02, respectively). Notably, the expression of SCT was identified as a risk factor of immune risk model, in which high risk showed poorer survival (P=0.04). High immunity status exhibited significant correlations in immune-responding pathways, HLA related genes and immune check point genes. Finally, included nine factors, our nomogram predicting model showed better calibration (C-index=0.764) and AUC=0.737. Conclusions: In this study, we investigated the patterns and prognostic roles of TMB and immune infiltration in colon cancer, which provided new insights into the tumor microenvironment, immunotherapies and a novel nomogram prognostic prediction model for colon cancer patients.